Chemical stability of drugs: Influence of light and temperature on montelukast stability in solution - Ivković Branka; Crevar-Sakač Milkica; Vujić Zorica (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2014)
In this paper, influence of temperature and light on stability of montelukast in solutions (standard substance, chewable tablets and film coated tablets) which were prepared during routine analysis of related substances was investigated. The content of montelukast and degradation products was determined by HPLC method at defined time intervals (influence of temperature was tested at the beginning, after 24 hours, and after 48 hours, and influence of light was tested at the beginning of the experiment and after 12 hours). Stability of montelukast in tested solutions under influence of temperature was acceptable. The content of montelukast ranged from 98 % to100 %, which meets the pharmacopoeia requirements and specifications. Individual and total impurities were within acceptable limits. Presence of photosensitive functional groups in structure of montelukast led to significant photodegradation. Individual and total impurities in samples which were under influence of light were above acceptable limits. Photodegradation occured during first 12 hours. Content of MOK-3 sulphoxide and unknown impurity on RRT 0.76 was above limits in all examined samples. Over a period of 12 h the content of those impurities grew 8-40 fold compared to time zero values.